2020
DOI: 10.1029/2020gb006649
|View full text |Cite
|
Sign up to set email alerts
|

Uranium Isotope Fractionation in Non‐sulfidic Anoxic Settings and the Global Uranium Isotope Mass Balance

Abstract: Uranium isotopes (238U/235U) have been used widely over the last decade as a global proxy for marine redox conditions. The largest isotopic fractionations in the system occur during U reduction, removal, and burial. Applying this basic framework, global U isotope mass balance models have been used to predict the extent of ocean floor anoxia during key intervals throughout Earth's history. However, there are currently minimal constraints on the isotopic fractionation that occurs during reduction and burial in a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
32
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 47 publications
(35 citation statements)
references
References 125 publications
3
32
0
Order By: Relevance
“…These suggestions are highly speculative and call for more field and experimental studies to better understand the controls on U removal and isotopic fractionation in shales. Interestingly, a recent study investigated the U isotopic composition of the modern and Silurian-Devonian shales, which were deposited in ferruginous settings and found that δ 238 U values were highly variable with a muted fractionation factor on average (Cole et al 2020). The authors also explored the effects on the mass balance model resulting from different reduction pathways with various apparent fractionation factors as well as different U mass accumulation rates.…”
Section: Non-uniformitarian U Isotopic Fractionation During Depositiomentioning
confidence: 99%
“…These suggestions are highly speculative and call for more field and experimental studies to better understand the controls on U removal and isotopic fractionation in shales. Interestingly, a recent study investigated the U isotopic composition of the modern and Silurian-Devonian shales, which were deposited in ferruginous settings and found that δ 238 U values were highly variable with a muted fractionation factor on average (Cole et al 2020). The authors also explored the effects on the mass balance model resulting from different reduction pathways with various apparent fractionation factors as well as different U mass accumulation rates.…”
Section: Non-uniformitarian U Isotopic Fractionation During Depositiomentioning
confidence: 99%
“…For uranium, the "oxic and other" sink includes Mn oxides, carbonates, pelagic sediments, coastal sediments, and alteration of oceanic crust. This particular mass balance for U takes into account the possibility that U burial in anoxic/noneuxinic settings (i.e., dissolved H 2 S confined to pore-waters) is typically associated with a smaller U isotope fractionation than euxinic settings (Hood et al, 2016;Cole et al, 2020). Other mass-balance models have assumed a large U isotope fractionation in all anoxic environments (euxinic and noneuxinic) (Tissot & Dauphas, 2015;Andersen et al, 2016;Noordmann et al, 2016).…”
Section: Oceanic Crust Alterationmentioning
confidence: 99%
“…At the end of the CIE, no clear stratigraphic shift occurs (Clarkson et al, 2018), suggesting global oceanic redox conditions did not significantly change. Mass-balance modeling, which assumes the magnitude of U isotope fractionation is similar for euxinic and anoxic/noneuxinic environments (an assumption currently being scrutinized; see Hood et al, 2016;Cole et al, 2020), suggests 8%-15% anoxic seafloor during OAE2 (Clarkson et al, 2018).…”
Section: Cenomanian-turonian (Oceanic Anoxic Event 2 Oae2; ~94 Ma)mentioning
confidence: 99%
See 2 more Smart Citations